Promise Boys - Brooks, Nick (UK, 2023)
The Urban Promise Prep School vows to turnboys into men. As students, J.B., Ramon and Trey are forced to follow the prestigious program's strict rules. Extreme discipline, they've been told, is what it takes to be college-bound, to avoid the fates of many men in their neighborhoods. This, the Principal Moore Method, supposedly saves lives. But when Moore ends up murdered and the police come sniffing around, the trio emerges as the case's prime suspects. With all three maintaining their innocence, they must band together to track down the real killer before ther are arrested...
Keywords: Action & Adventure; Juvenile Fiction; School & Education